Reduced leakage current, enhanced ferroelectric and dielectric properties of (La, Fe)-codoped Bi0.5Na0.5TiO3-based thin films. (July 2015) - Li, Peng; Li, Wei; Liu, Shaohui; Zhang, Yang; Zhai, Jiwei; Chen, Haydn
Abstract: The lead-free Na0.5 Bi0.5 TiO3 –K0.5 Bi0.5 TiO3 –SrTiO3 (BNT–BKT–ST) and (La, Fe)-codoped Na0.5 Bi0.5 TiO3 –K0.5 Bi0.5 TiO3 –SrTiO3 (BNT–BKT–ST–LaFe) thin films were deposited on Pt/Ti/SiO2 /Si substrates by the sol–gel method. Both the BNT–BKT–ST and BNT–BKT–ST–LaFe thin films exhibit pseudo-cubic perovskite structure and uniform grain size. The leakage current density of BNT–BKT–ST–LaFe thin film at 400 kV/cm is reduced by approximately two orders of magnitude compared with BNT–BKT–ST thin film. Enhanced ferroelectric property is achieved in BNT–BKT–ST–LaFe film with a large remanent polarization of 13 μC/cm 2 . At the same time, the BNT–BKT–ST–LaFe film also exhibits a large dielectric constant of 420 and small dielectric loss of 0.055 at 100 kHz. These results indicate that the (La, Fe)-codoped BNT–BKT–ST thin film is a promising candidate in lead-free ferroelectric materials.